2023
DOI: 10.3389/fonc.2023.1228076
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-to-lymphocyte ratio as a new prognostic factor in cancers: a narrative review

Kian Heshmat-Ghahdarijani,
Vida Sarmadi,
Afshin Heidari
et al.

Abstract: The increasing incidence of cancer globally has highlighted the significance of early diagnosis and improvement of treatment strategies. In the 19th century, a connection was made between inflammation and cancer, with inflammation recognized as a malignancy hallmark. The neutrophil-to-lymphocyte ratio (NLR), calculated from a complete blood count, is a simple and accessible biomarker of inflammation status. NLR has also been proven to be a prognostic factor for various medical conditions, including mortality c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
0
1
0
Order By: Relevance
“…It is well known that chronic systemic inflammation plays a key role in the mechanism of metabolic diseases [12]. NLR, assessed by neutrophils and lymphocytes, is considered a cost-effective index to reflect the status of systemic inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that chronic systemic inflammation plays a key role in the mechanism of metabolic diseases [12]. NLR, assessed by neutrophils and lymphocytes, is considered a cost-effective index to reflect the status of systemic inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that chronic systemic inflammation plays a key role in the mechanism of metabolic diseases 16 , 17 . NLR, assessed by neutrophils and lymphocytes, is considered a cost-effective index to reflect the status of systemic inflammation 18 . For instances, a Chinese large sample study (n = 90,237) found that NLR was related to the prevalence of T2DM in men and women 19 ; T Akase et al 20 reported that NLR might be a useful biomarker for diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%